Eco-Economic Security of the Region: Expanding the Management System for Assessing the State of Development - Pavel Ryabchuk; Artem Salamatov; Daria Gordeeva; Elena Gnatyshina; Andrei Fedoseev; Dmitrii Korneev; Yana Borisenko; Liliia Bazavlutskaia; Valerii Yakupov (International Journal of Supply Chain Management, 2018)
Abstract- The problem of ensuring environmental and economic security for quite a long time remains relevant in the world community. It is the subject of continual scientific debates. The alignment of IT strategy which is a necessity. Information technology is useful for companies when they can be used in the right way. In this regard, learning can be an effective step in transferring knowledge to human and financial management. Unfortunately, in many cases the priority in strategic planning, namely in the mechanisms for implementing the existing strategies, is given to the interests of large manufacturers, whose goals (increase in profits, business costs, etc.) are often diametrically opposed to socio-ecological goals (for example, decrease of harmful emissions through spending more money on treatment plants in order to prevent natural degradation and morbidity of the population, etc.). The solution of this problem should be based on the concept of balanced eco-economic development and changes in the paradigm of entrepreneurship education. It is very important that any economic project is environmentally sound, and any environmental decision is economically feasible. At the same time every environmental decision should take into account the development of the well-being of citizens and the development of the region. All this requires the development of a whole system of stimulating the social and environmental responsibility of contaminating plants, both at the level of the state as a whole and at the regional level. In Russia, scientific research on this issue has been actively conducted for 10-15 years. Based on this research, some standard methods for assessing the eco-economic development of the territories were developed. However, in the context of current conditions, they need radical changes and new approaches. Let us consider this problem in more detail.